Query Expansion Pada Line Today Menggunakan Algoritme Ide-Dec-Hi dan Ide-Regular - Nana Nofiana; Indriati Indriati; Rizal Setya Perdana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
LINE TODAY is an online news site that provides up to date news articles and comes from trusted news sources. To make it easier to find news, a search engine is needed so news is quick to get. But in the search process, sometimes the queries entered are not in accordance with the results of news articles obtained. So it is necessary to do query expansion to help get more specific news articles, query expansion will expand previously ambiguous queries to be more structured. Query expansion begins with preprocessing stages, followed by weighting TF.IDF, as well as cosine similarity to the calculation of the idea-dec-hi and ide-regular method. Based on the implementation and testing carried out on the Query Expansion research on LINE TODAY, Using Ide-Dec-Hi and ide-regular Algorithm by utilizing 200 training data and 25 queries that are in accordance with the document, then the results for idea-dec-hi method that is the precision value is 0.6622, recall is 0.2314, f-measure is 0.2987, and the accuracy is 0.9506. Where as for ide-regular method results in precision values of 0.6635, recall of 0.0146, f-measure of 0.0279, and accuracy of 0.9488. Accuracy values generated using the ide-dec-hi method increase up to 0.18% compared to the ide-regular method.